The laryngeal tube - a helpful tool for cardiopulmonary resuscitation in the dental office? - Keilholz, Georg; Mutzbauer, Till Sebastian (British dental journal, 2015)
The laryngeal tube may provide beneficial effects during ventilation within CPR administered by dental staff.Lay rescuers, as well as inexperienced professional first responders, must be instructed to continue chest compression during insertion of supraglottic airway adjuncts such as the laryngeal tube.
Gesehen am 07.07.2002